The last act : a novel - Parks, Brad, 1974- (Dutton, 2019)
Tommy Jump is an out-of-work stage actor approached by the FBI with the role of a lifetime: Go undercover at a federal prison, impersonate a convicted felon, and befriend a fellow inmate, a disgraced banker named Mitchell Dupree who knows the location of documents that can be used to bring down a ruthless drug cartel. . . if only he<U+2019>d tell the FBI where they are. The women in Tommy<U+2019>s life, his fiancée and mother, tell him he<U+2019>s crazy to even consider taking the part. The cartel has quickly risen to become the largest supplier of crystal meth in America. And it hasn<U+2019>t done it by playing nice. Still, Tommy<U+2019>s acting career has stalled, and the FBI is offering a minimum of $150,000 for a six-month gig<U+2014>whether he gets the documents or not. Using a false name and backstory, Tommy enters the low-security prison and begins the process of befriending Dupree. But Tommy soon realizes he<U+2019>s underestimated the enormity of his task and the terrifying reach of the cartel. The FBI isn<U+2019>t the only one looking for the documents, and if Tommy doesn<U+2019>t play his role to perfection, it just may be his last act.